THE EFFECT OF BRAND ATTACHMENT, BRAND EXPERIENCE, AND SELF-IMAGE CONGRUENCE ON THE PURCHASE INTENTION OF LUXURY BRAND - Yuanita, Asih Dewi; Marsasi, Endy Gunanto (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
This study empirically builds a conceptual model that describes the effects of brand attachment, self-image congruence, and brand experience on purchase intention. The focus of this research is to examine the debate over the findings of previous researchers regarding the influence of hedonic motivation and self-image congruence in attachment theory-based models using brand attachment as the central variable. The contribution of this study is to investigate the relationship between hedonic motivation and self-image congruence because, so far, no research has tested the effect of hedonic motivation on self-image congruence. Attachment theory and self-congruity theory are used to solve this problem. The sample selection used a purposive sampling strategy with the characteristics of respondents in Indonesia who had used luxury brands. The number of samples that were successfully collected and tested included 354 respondents. The hypothesis was tested using the Structural Equation Model (SEM) analysis technique. The findings confirm that hedonic motivation and self-image congruence are drivers of brand attachment and increase consumers' purchase intentions.JEL : M30, M31.  ABSTRAKPenelitian ini mencoba mengembangkan model konseptual secara empiris tentang pengaruh brand attachment, self-image congruence, dan brand experience terhadap niat beli. Peneliti menemukan bahwa keterikatan merek dan keselarasan citra diri tidak optimal untuk perusahaan merek mewah, meningkatkan kemungkinan mereka memengaruhi niat beli konsumen merek mewah. Fokus penelitian ini adalah mengkaji perdebatan atas temuan peneliti sebelumnya mengenai pengaruh variabel motivasi hedonis dan keselarasan citra diri pada model berbasis teori keterikatan dan menggunakan keterikatan merek sebagai variabel inti. Penelitian ini juga menggabungkan teori keterikatan dan teori keselarasan diri untuk memecahkan masalah tersebut. Pemilihan sampel menggunakan strategi purposive sampling dengan karakteristik responden Indonesia yang pernah menggunakan merek-merek mewah. Sebanyak 354 dari 375 responden berhasil dikumpulkan dan diuji sampelnya, sekitar 21 kuesioner berisi data yang tidak memenuhi syarat. Pengujian hipotesis akan menggunakan teknik analisis SEM (Structural Equation Model). Temuan mengkonfirmasi bahwa motivasi hedonis dan keselarasan citra diri adalah pendorong keterikatan merek, dan dapat meningkatkan niat beli konsumen.Kata Kunci : keterikatan merek, kesesuaian citra diri, motivasi hedonis, pengalaman merek, niat beli